Analisis pengaruh organizational resilience, job satisfaction, organizational learning culture, dan turnover intention terhadap business performance pada perusahaan pertamina - Suciariani, Suciariani; Anggraeni , Dwi Septi; Tanuwijaya, Justine (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aimed to analyze the influence of Organizational Resilience, Job Satisfaction, Organizational Learning Culture, and Turnover Intention on Business Performance. Business Performance. The data analysis technique in this study used several statistical tests to apply structural equation modeling (SEM) as a tool. The sample data collection method in this study used purposive sampling with a sample of employees of PT. Pertamina. This study used a questionnaire distributed online. The sample from the population was carried out with specific considerations, namely all employees of the financial services industry in Indonesia, as many as 135 respondents. The results show that organizational learning culture has a positive effect on job satisfaction, organizational learning culture has a positive effect on turnover intention, job satisfaction has a positive effect on turnover intention, job satisfaction has a positive effect on business performance, organizational resilience has a positive effect on job satisfaction, and organizational resilience affects positively on business performance.